Analisis Asimetri Harga Ikan Tuna di Sumatera Barat - Junaidi, Junaidi; Saputra, Wiko (Jurnal Ekonomi dan Pembangunan Indonesia, 2010)
The limited number of auction agents of tuna fish and the lack of infrastructure in auction center trigger the occurrence of third parties in marketing system. The collusion on price among agents ocrurs in auction center, especially in harvest season. The asymmetric information of the price between agent to consumer has occurred for a long time in West Sumatra and even in various regions in Indonesia. The challenges are how to develop fisheries and minimize poverty which occur on fisherman. The aim of this research was to analyze the asymmetry of price of tuna fish at agents, sub-agents and retailers coming from three auction centers toward four regional markets in West Sumatra. Methodology used in this research was Boyd and Brorsen's theory by using data on daily price of tuna fish. The result of thisstudy reveals that asymmetry of price was found at auction centre in West Sumatra. This result indicated that the increasing of price at sub-agents was not followed with the increasing of price at agents. However, the increasing of price at sub-agents was directly followed with the increasing of price at retailers.